PROMOTING STUDENTS’ WRITING SKILL: GENRE-BASED APPROACH IN INDONESIA EFL CONTEXT - Gintings, Mohammad Fajar Mediyawan (Lexeme : Journal of Linguistics and Applied Linguistics, 2020)
This paper aimed to critically examine the effectiveness of Genre-Based Approach (GBA) to teaching writing in EFL context of Indonesia. Although several studies have discussed the effectiveness of GBA in teaching writing, those studies put emphasize how GBA focuses on genre or text types rather than the basic principles of GBA that aims for socially functioning language skills. This paper draws on the relevant literature to investigates how GBA suits the teaching of writing in EFL context of Indonesia. Moreover, the discussion focuses on the benefits of GBA which mainly derived from five key principles of Genre proposed by Hyland (2007). Through the exploration of existing empirical studies, this paper found that GBA offer three main benefits in teaching writing under the EFL context. These benefits are: (1) the offer of practical writing skill; (2) the build of students? confidence in English writing; and (3) stimulation on students? critical thinking as part of their English literacy. Nevertheless, the benefits of GBA in teaching writing could only be attained if teachers implement GBA according to its full-fledged teaching and learning cycles.